Laparoscopic management of giant ovarian cyst in young woman: a case report - Gothwal, Meenakshi; Nalwa, Aasma; Yadav, Garima; Lodha, Mahendra; Singh, Pratibha; Garg, Pawan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Giant ovarian cysts are very rare nowadays and were conventionally treated by full midline laparotomy. In recent years, the laparoscopic approach is also practiced but it needs a lot of expertise and only a few cases have been reported. As the surgical treatment of choice has become less invasive, laparoscopic surgery is considered more beneficial over laparotomy because of better cosmetic results, less blood loss, reduced postoperative analgesic requirement, early mobilization and faster discharge from the hospital and early resumption to normal day to day activity. We report a case of laparoscopic extirpation of a giant right ovarian cyst measuring 15 × 21 × 22 cm in young 24-year female.